2021
DOI: 10.1057/s41267-021-00405-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term energy transitions and international business: Concepts, theory, methods, and a research agenda

Abstract: International business and management (IB/IM) scholars are increasingly calling for more research attention to subject matter that incorporates global-scale issues (Buckley, Doh, & Benischke, 2017). These calls have frequently focused on societal “grand challenges” that transcend discrete geographical locations and well-defined (typically short) time periods. The present long-term energy transition (LTE), characterized by a shift away from hydrocarbons and towards renewables, represents an important example of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 125 publications
(90 reference statements)
0
18
0
Order By: Relevance
“…However, following the growth of CSR in the West, Chinese firms have realised that civil society perceives CSR as a counterweight to firm performance (Li et al, 2019). Notwithstanding the aforementioned scepticism towards CSR in China, at least for the last 10 years, Chinese firms have been pursuing a balance between CSR and firm performance (Doh et al, 2021). Thus, normative social pressure in China acts as an external force driving Chinese firms' CSR and boosting their financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, following the growth of CSR in the West, Chinese firms have realised that civil society perceives CSR as a counterweight to firm performance (Li et al, 2019). Notwithstanding the aforementioned scepticism towards CSR in China, at least for the last 10 years, Chinese firms have been pursuing a balance between CSR and firm performance (Doh et al, 2021). Thus, normative social pressure in China acts as an external force driving Chinese firms' CSR and boosting their financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Notably, the world experienced two visible energy transitions in the previous 150 years. The first transition includes the shift from coal to oil and gas (Yergin, 2011) and the second conversion from hydrocarbons to renewables (Doh et al, 2021). In the second transitionary phase, the comparative share of gas and oil in the global energy mix has reduced, but its usage has rocketed (Armaroli & Balzani, 2016;Verbong & Loorbach, 2012;Wood et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The focus on Italian SMEs primarily from the service sector (e.g., information and communication services) brings our focus back to the debate surrounding the knowledge-based economies (Harris, 2001) and the prominence of the service sector in the international business context (cf. Doh et al, 2021). The authors found that both equity and reward crowdfunding are vital for the internationalization of SMEs, given their role in providing financial resources, developing international networks, increasing foreign market awareness, and establishing international agreements/ brands.…”
Section: An Overview Of the Articles Included In This Focused Issuementioning
confidence: 99%